EFFECT OF OSATERONE ACETATE ON SERUM TESTOSTERONE LEVELS AND SEMINAL PARAMETERS IN DOGS WITH BENIGN PROSTATIC HYPERPLASIA - T.R. Dhivya; P. Sridevi; K. Kulasekar; P.Kumarasamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was carried out with the aim to investigate the effect of Osaterone acetate (OSA), an antiandrogen on blood testosterone levels and the seminal parameters in dogs with benign prostatic hyperplasia (BPH). OSA treatment of dogs with BPH showed no significant changes in mean volume, concentration, live and dead and sperm motility. However, a transient increase in sperm abnormality was noticed by month 2 which gradually decreased to pretreatment levels by month 4 - 5. Similarly, a significant and transient decline in the mean testosterone levels were noticed following OSA administration indicating that the transient decrease in the testosterone level might be responsible for a transient increase in the sperm abnormality. No adverse effects were noticed following OSA administration and 100 per cent of the dogs experienced complete clinical remission of BPH and stayed in remission throughout the 6 month trial period.